The Effect of Occupational Safety and Health to Employee Performance in PT.IMP - Tobing, Josephine; Lumbantoruan, Rutman; Sihotang, Khesia Pinta Uli Rian (Fundamental Management Journal, 2016)
The purpose of this study was to determine how much influence the health and safety to employees performance in PT Internet Media Prima. The sampling technique using saturated sampling technique (census), because the sampling is done in the Project division in which only amounted to 30 people. This research uses descriptive analysis with quantitative approach using a questionnaire and using linear regression analysis techniques, that occupational safety and health as independent variables (X) and employee performance as the dependent variable (Y). The data processing in this study using the program Statistical SPSS. The results of this study states that the safety and health give singnificant and positive effect on employee performance.Keywords: health, safety, employee performance